Sex-Specific Behavioral Features of the Prenatal Valproic Acid Rat Model of Autism Spectrum Disorder - Patience Mulalo Mamali; Christine Dignon; Ayanda Ngwenya; Busisiwe Constance Maseko (Brain Sciences)
Background/Objectives: Autism is a complex neurodevelopmental disorder characterized by restricted behaviors and impaired social and communication skills. The exact cause of autism remains unknown. One promising animal model for studying autism is the valproic acid rat model. Due to a 1 to 4 bias for males in autism occurrence, most animal model studies investigate only males and neglect females. However, female autism often appears different from that observed in males. Females are said to be less regularly diagnosed because they can “mask” their symptoms. Female autism is as necessary to investigate as male autism. Methods: Fertile adult female Sprague-Dawley rats were impregnated and injected with valproic acid on gestational day 13. Male and female offspring were subjected to behavioral tests to investigate autistic symptoms. Tests included novel object recognition, balance-beam, Y-maze, hole-board, three-chamber, marble burying, olfactory, light/dark and hot plate tests. Results: The tests revealed that VPA-exposed rats had increased anxiety-like behaviors, hyperactivity, and impaired non-verbal communication. However, they did not display repetitive behaviors or cognitive impairments. Notably, male and female rats showed different autism-like traits, with both showing hyperactivity, and males (but not females) additionally showing impaired sociability and increased anxiety. Conclusions: The findings suggest that prenatal exposure to VPA induces autism-like behaviors in both male and female Sprague-Dawley rat offspring. However, males appear more impacted by VPA exposure as evinced by their display of more autism-like symptoms relative to females. This study provides support for including both sexes in all studies modelling autism, as outcomes are seemingly impacted by the sex being observed.